Reduced plasma levels of neuregulin-1 are associated with adverse outcomes in patients with atherosclerotic cardiovascular disease - Liu, Jie; Liu, Huiyi; Geng, Hui; Fan, Yan; Liu, Meilin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundNeuregulin-1 (NRG-1), a stress-mediated paracrine transmembrane growth factor, plays vital roles in the pathophysiology of atherosclerosis, myocardial infarction, ischemia-reperfusion, heart failure (HF), cardiomyopathy and other cardiovascular diseases. This study aimed to assess plasma NRG-1 levels in atherosclerotic cardiovascular disease (ASCVD) patients and explore the relationship between NRG-1 levels and patient outcomes.MethodsPlasma NRG-1, monocyte chemotactic protein-1 (MCP-1), myeloperoxidase (MPO) and vascular cellular adhesion molecule-1 (VCAM-1) concentrations were quantified in 185 ASCVD patients and 185 age- and sex-matched controls. All ASCVD patients were followed up for 14–16 months, and major adverse cardiovascular and cerebrovascular events (MACCEs), including angina pectoris, nonfatal myocardial infarction, nonfatal stroke, new HF symptoms, and CVD-related death, were recorded.ResultsASCVD patients presented notably lower NRG-1 levels (123.45 ± 0.87 pg/ml, vs. 139.76 ± 0.83 pg/ml for controls, P < 0.001) and higher MCP-1, MPO and VCAM-1 levels. Circulating NRG-1 levels were negatively associated with MCP-1 (−0.278, P < 0.001), MPO (−0.171, P = 0.001) `and VCAM-1 (−0.351, P < 0.001) levels. Logistic regression analysis revealed that a high NRG-1 level was a significant protective effect against ASCVD (OR = 0.859, 95% CI = 0.821–0.900; P < 0.001). In the mediation analysis, MCP-1, MPO, and VCAM-1 explained 20.2%, 8.8%, and 30.1%, respectively, of NRG-1's association with ASCVD. After an average follow-up of 13.8 ± 1.7 months, the mean NRG-1 level was lower in patients with MACCEs than in patients without MACCEs (112.04 ± 1.24 pg/ml vs. 125.93 ± 0.90 pg/ml, P < 0.001). Kaplan-Meier survival analysis revealed that patients with plasma NRG-1 concentration <122.5 pg/ml had a lower survival rate than those with higher levels (P < 0.001). According to the adjusted models, NRG-1 was independently associated with a decreased risk of MACCEs [adjusted HR 0.857 (95% CI 0.809–0.908), P < 0.001].ConclusionsReduced NRG-1 levels in ASCVD patients increased the risk of MACCEs. NRG-1 levels may serve as useful laboratory markers of ASCVD prognosis.